The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ner.13328
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Repetitive Transcranial Magnetic Stimulation at Different Stimulus Parameters for Neuropathic Pain: A Randomized Study

Abstract: Objectives:The aim of the present study was to investigate the analgesic effects of repetitive transcranial magnetic stimulation over the primary motor cortex (M1-rTMS) using different stimulation parameters to explore the optimal stimulus condition for treating neuropathic pain. Materials and Methods:We conducted a randomized, blinded, crossover exploratory study. Four single sessions of M1-rTMS at different parameters were administered in random order. The tested stimulation conditions were as follows: 5-Hz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…However, the impact of TMS frequency and pulse number remains poorly understood and may present an opportunity to optimise analgesic efficacy and promote long-term effects. Prior work indicated that a single session consisting of 2,000, but not 500 pulses of 10Hz rTMS, was necessary to induce a significant alleviation of neuropathic pain relative to sham stimulation [7]. At least 1,000 pulses per session is recommended by the European Academy of Neurology, with the suggestion that increasing the pulse number may increase analgesic efficacy [2].…”
Section: Cortex Rtmsmentioning
confidence: 99%
“…However, the impact of TMS frequency and pulse number remains poorly understood and may present an opportunity to optimise analgesic efficacy and promote long-term effects. Prior work indicated that a single session consisting of 2,000, but not 500 pulses of 10Hz rTMS, was necessary to induce a significant alleviation of neuropathic pain relative to sham stimulation [7]. At least 1,000 pulses per session is recommended by the European Academy of Neurology, with the suggestion that increasing the pulse number may increase analgesic efficacy [2].…”
Section: Cortex Rtmsmentioning
confidence: 99%
“…We extracted randomized controlled trials (RCTs) of rTMS using the figure-of-8 coil for neuropathic pain, conducted at Osaka University Hospital as the main study institution, because this was the first attempt to review the analgesic effects at different pain sites. We included three of our previous clinical trials in this meta-analysis (Hosomi et al, 2013(Hosomi et al, , 2020Mori et al, 2021b). Hosomi et al (2013) conducted a randomized, double-blind, sham-controlled trial, from 2009 to 2011, at seven centers in Japan, to assess the efficacy and safety of 10 daily doses of rTMS in patients with neuropathic pain.…”
Section: Study Design Studies Selection and Data Sourcementioning
confidence: 99%
“…The mean decrease in VAS score was calculated using the procedure described by Hosomi et al (2013). Finally, in a trial by Mori et al (2021b), a randomized, single-blind, sham-controlled, crossover exploratory study was conducted from 2017 to 2018 at Osaka University Hospital to explore the optimal stimulus conditions for treating neuropathic pain. Four single sessions of M1-rTMS at different parameters (1, 5-Hz with 500 pulses per session; 2, 10-Hz with 500 pulses per session; 3, 10-Hz with 2000 pulses per session; and 4, sham stimulation) were conducted in random order.…”
Section: Study Design Studies Selection and Data Sourcementioning
confidence: 99%
See 2 more Smart Citations